Increased protein degradation and decreased protein synthesis in skeletal muscle during cancer cachexia. - Smith, K. L. (Nature Publishing Group, 1993)
The effects of progressive cachexia on protein metabolism in skeletal muscle has been investigated in mice bearing the MAC16 adenocarcinoma which produces cachexia with tumour burdens of < 1% of the host weight. Weight loss was accompanied by loss of whole body nitrogen in proportion to the overall loss of body mass. Using L-[4-3H]phenylalanine to label proteins in gastrocnemius muscle, a significant depression (60%) in protein synthesis occurred in animals with a weight loss between 15 and 30% accompanied by an increase in protein degradation, which increased with increasing weight loss between 15 and 30%. Muscle degradation in vitro could be achieved by serum from cachectic animals, which appeared to contain a proteolysis-inducing factor. These results suggest that the increased degradation of skeletal muscle seen in this model of cachexia may be due to a circulating proteolysis-inducing factor.